Wages, rents, unemployment, and the quality of life - Matthias Wrede (Friedrich-Alexander-Universität Erlangen-Nürnberg, Institut für Wirtschaftspolitik und Quantitative Wirtschaftsforschung (IWQW), 2012)
Combining a spatial equilibrium model with a search-matching unemployment model, this paper analyzes the willingness to pay for regional amenities and the regional quality of life when wages, rents, and unemployment risk compensate for local amenities and disamenities. The results are compared with those obtained from the Rosen-Roback approach. Furthermore, the paper shows that the wage curve is negatively sloped for quasi-linear utility. Specifically, the wage rate increases and the unemployment ratio decreases in response to an increase in the amenity level if the amenity is marginally more beneficial to producers than to consumers. As an illustration of the unemployment-adjusted quality-of-life measure, the quality of life in West German counties is estimated.
Keywords: R12; R13; R14; H73; J61; J64; 330; quality of life; residential mobility; unemployment; job search; matching; Lebensqualität; Region; Regionale Arbeitslosigkeit; Regionale Lohnstruktur; Miete; Schätzung; Deutschland